ANALISIS PEMBELAJARAN BAHASA JERMAN BERBASIS HYBRID LEARNING (STUDI KASUS PADA SISWA KELAS X SMA ANGKASA HUSEIN SASTRANEGARA) - Niken Khaerunnisa Salsabila; Irma Permatawati; Pepen Permana (Jurusan Pendidikan Bahasa Jerman FPBS UPI, 2023)
German hybrid learning model combines two learning methods that consist offline and online. On the other hand, there are still many aspects in this learning model that need further analysis, for instance student’s score acquisition during hybrid learning and student’s perception on German hybrid learning model as a result of empirical data which can be seen and valued. This research is conducted based on previous discussed aspects to identify: 1) 10th grade students learn result during the German hybrid learning at Angkasa Husein Sastranegara High School; 2) 10th grade student’s perception on German hybrid learning at Angkasa Husein Sastranegara High School. This research uses qualitative analysis with descriptive cases study. Result of this research’s analysis determined that 1) Student’s score acquisition during German hybrid learning has no significant difference in overall, rather there’s differences during the offline and online learning; 2) Student’s perception on German hybrid learning conclude that learning goes effectively and reveal another learn environment caused by offline and online learning furthermore hybrid learning model offers a student-focused learning method to help student to explore insight independently. Nonetheless students find F2F learning more effective for foreign language learning, notably German. Overcoming this requires the development of learning methods in hybrid learning.